Age-dependent accumulation of genomic aberrations and deregulation of cell cycle and telomerase genes in metastatic neuroblastoma - Coco, Simona; Theissen, Jessica; Scaruffi, Paola; Stigliani, Sara; Moretti, Stefano; Oberthuer, André; Valdora, Francesca; Fischer, Matthias; Gallo, Fabio; Hero, Barbara; Bonassi, Stefano; Berthold, Frank; et al. (International journal of cancer, 2012)
About 50% of children with neuroblastoma (NB) show a metastatic disease and have a poor prognosis. However, disease progression is greatly variable and depends on patients' age and MYCN oncogene amplification. To investigate the role of patients' age in tumor aggressiveness, we performed array‐CGH and gene expression profiles of three groups (G) of metastatic NBs: G1, stage 4S patients and MYCN single copy (MYCN−) tumors; G2, stage 4 patients, ≤18 months of age, MYCN− tumors and favorable outcome and G3, Stage 4 patients, ≥19 months with unfavorable outcome. G1 was characterized by numerical aberrations prevalently; on the contrary, all G3 tumors had structural rearrangements, whereas G2 showed an intermediate pattern. The average of numerical alterations decreased significantly from G1 to G2 to G3 (p < 0.01). Contrarily, the number of structural aberrations increased from G1 to G2 to G3 (p < 2.35 E−05). Noteworthy, G3/MYCN− NBs were characterized by several complex intrachromosome rearrangements. Expression analysis of the three groups showed significant differences in genes of Rho and Ras signaling pathways, development and adhesion, cell cycle regulation and telomerase activity. Accumulation of structural alterations increased with patients' age and was associated with a more aggressive disease. Abnormal expression of genes involved in cell cycle and telomerase in G3 may be responsible for the genomic instability in this cohort of patients. The higher DNA instability observed in G3/MYCN− NBs than in MYCN‐amplified G3 may also explain why patients ≥19 months have a poor outcome independently by MYCN status.